Comparative Evaluation of the Antimicrobial Activity of Triphala Hydrogel Against Amoxicillin: An In Vitro Study (Academia Journal of Medicine, 2026)
Background: Ayurveda is a traditional Indian system of medicine that utilizes plant-based formulations  for preventive and curative healthcare. Triphala, a tridoshic rasayana composed of Emblica  officinalis, Terminalia chebula, and Terminalia bellerica, possesses well-documented  antimicrobial properties attributed to tannins, flavonoids, phenols, and other polyphenolic  compounds. Considering the growing concern of antimicrobial resistance, herbal alternatives  are gaining attention in dental therapeutics. Aim: To comparatively evaluate the antimicrobial activity of Triphala hydrogel against Escherichia  coli and Bacillus subtilis using amoxicillin as the standard control. Materials and Methods: An in vitro study was conducted using Triphala hydrogel formulations prepared at  concentrations ranging from 2–10% w/v (F1–F5). Antimicrobial efficacy was assessed by  agar diffusion method against Bacillus subtilis and Escherichia coli. Zones of inhibition  (ZOI) were measured in millimetres and compared with amoxicillin as the positive control. Results: A concentration-dependent increase in antimicrobial activity was observed against both  organisms. Against Bacillus subtilis, ZOI increased from 9.2 ± 0.5 mm (2% w/v) to 21.6 ±  0.9 mm (10% w/v). Against Escherichia coli, ZOI increased from 8.7 ± 0.5 mm to 19.4 ± 0.9  mm across the same concentration range. Amoxicillin demonstrated significantly higher  inhibition zones (27.5 ± 1.2 mm and 26.8 ± 1.1 mm against Bacillus subtilis and Escherichia  coli, respectively). Triphala formulations exhibited moderate yet significant antimicrobial  activity, with the 10% w/v formulation showing optimal efficacy. Conclusion: Triphala hydrogel demonstrated dose-dependent antimicrobial activity against both  gram-positive and gram-negative bacteria. Concentrations of 8–10% w/v appear optimal  for therapeutic applications. Triphala-based hydrogels may serve as promising adjunctive  herbal antimicrobial agents in dental care, particularly in the context of increasing antibiotic  resistance.
Keywords: riphala hydrogel; antimicrobial activity; zone of inhibition; agar diffusion assay; herbal dentistry; amoxicillin comparisonRemove Triphala hydrogel; antimicrobial activity; zone of inhibitionagar diffusion assay; amoxicillin comparison